Bianco e colori. Sigismondo Malatesta, Alberti, e l’architettura del Tempio Malatestiano - Bulgarelli, Massimo (Opus Incertum, 2017)
The use of white Istrian stone on the exterior of the Tempio Malatestiano in Rimini is due to a variety of reasons. On the one hand it is a reference to the evocative power of the colour white in ancient Roman architecture, recalling the origins of the city - the arch of Augustus and the bridge of Augustus and Tiberius - as well as, in more general terms, an Imperial attribute, already recorded in ancient literary sources, and well known by Leon Battista Alberti and the humanists at the court of Sigismondo Malatesta. On the other hand, the colour white is one of the aspects of the identification of the patron and the building. Together with white, in fact, red and green are also used – in the marble crustae of the gateway and in the painted traces of wall surfaces found recently on the sides of the building - showing the heraldic colours of the Malatesta. The Temple, like Castel Sismondo, was adopted as an emblematic image in Sigismondo’s medals together with the family livery.